2021
DOI: 10.1038/s41598-021-94252-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association studies of alterations in protein function expose recessive effects on cancer predisposition

Abstract: The characterization of germline genetic variation affecting cancer risk, known as cancer predisposition, is fundamental to preventive and personalized medicine. Studies of genetic cancer predisposition typically identify significant genomic regions based on family-based cohorts or genome-wide association studies (GWAS). However, the results of such studies rarely provide biological insight or functional interpretation. In this study, we conducted a comprehensive analysis of cancer predisposition in the UK Bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 73 publications
1
20
1
Order By: Relevance
“…In this study, we used both GWAS and PWAS association methodologies and extensively compared them [25, 26]. We showed that PWAS as a gene-based method can detect non-additive effects (Figure 3) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used both GWAS and PWAS association methodologies and extensively compared them [25, 26]. We showed that PWAS as a gene-based method can detect non-additive effects (Figure 3) .…”
Section: Discussionmentioning
confidence: 99%
“…We examined the entire distribution of PWAS effect scores by considering all possible cutoffs for the relevant cohort, i.e., all subsets with effect scores that are either below or above a certain threshold. We describe the relevant sub-populations by percentiles (e.g., "bottom 10%" refers to the 10% of the cohort with the lowest PWAS scores) [26].…”
Section: Gene-based Polygenic Risk Estimates For Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the two copies of a gene are affected by different variants, a case known as compound heterozygosity, then a variant-level recessive model would be completely blind to it. Due to the inherent blindness of GWAS to compound heterozygosity, the study of recessive genetic effects in complex human traits is highly neglected, but some recent works show that they are in fact common in complex traits [ 95 , 96 ]. Gene-based methods (as opposed to variant-based methods) seem especially promising for detecting recessive effects [ 45 ].…”
Section: Non-additive Genetic Effects: Oversight or Non-issue?mentioning
confidence: 99%
“…Determining the phenotypic consequences of genetic variants is a key challenge in human genetics [1][2][3][4]. While most genetic variants associated with common human disease occur in non-coding regions of the genome, variants that affect the amino-acid (AA) sequence of proteins are enriched amongst variants associated with common human disease and cause many rare Mendelian and somatic disorders [5][6][7][8]. Coding variants are also of special interest because the mechanisms by which they act are better understood, and they are more therapeutically actionable.…”
Section: Introductionmentioning
confidence: 99%